The Role of Civics Teachers in Strengthening the Character of Tolerance in Grade XI Students of Daya Asuhan High School - Dewi, Putri Tiara; Amin, Zulkifli (Lembaga Riset Mutiara Akbar, 2023)
This study aims to examine the role of Civics teachers in strengthening the character of tolerance in grade XI students of Asuhan Daya High School, the character of tolerance is one of the important aspects in the formation of student personality amidst the diversity of cultures, religions, and ethnicities in Indonesia. Civics teachers have a great responsibility in instilling the values ??of tolerance through classroom learning. This study uses qualitative methods, data collection using observation, interviews, and documentation methods. The results of this study in strengthening the character of tolerance, the teacher is the one who then bridges in instilling the value of tolerance to students, it is stated that there are five steps in implementing tolerance attitude education in the classroom, namely the first, analyzing basic competencies by identifying character values ????in the subject matter. Then the second, planning a learning implementation plan that focuses on the content of tolerance, the third following the learning according to what has been planned, the fourth carrying out the assessment process, and the last evaluating learning outcomes to determine the extent to which students understand what the teacher teaches.